Experimental analysis of burr formation in drilling of TI-6AL-4V alloy. (2016) - Patil, Rahul; Shinde, Sagar; Marla, Deepak; Joshi, Suhas
Burr formation is a prominent phenomenon in drilling of titanium and its alloys. It is not possible to de-burr the component completely but the deburring efforts can be reduced substantially by minimising the burr formation. This experimental-based study analyses the stages involved in the burr formation, the mechanism of burr formation and the type of burr formed. The effect of process parameters on burr formation is analysed using response surface methodology. For the experiments performed, three levels of cutting speed, feed, point angle, corner chamfer angle and cutting edge chamfer angle are used. The size of the burr was observed to be smaller using modified drills in comparison to the conventional drills. Also, while the burr size increases with an increase in cutting speed and cutting edge chamfer angle, it decreases with an increase in feed rate. The minimum burr height was observed at 40° corner chamfer angle.